Exploring the function and pathogenicity of Goatpox virus N1L gene using recombinant vaccinia virus Tiantan strain - Xin, Jialiang; Shi, Yaqi; Du, Qian; Liao, Yanjuan; Zhao, Zhongyi; Bi, Jingshan; Peng, Jiuqing; Cheng, Sheng; Hu, Chuanhuo; Zheng, Min (Frontiers in Veterinary Science, 2025)
The N1L gene is a well-characterized virulence factor in the poxvirus family; however, its functional role in Goatpox virus (GTPV) remains poorly understood. To elucidate the biological significance of the GTPV N1L gene (gN1L), we constructed three recombinant vaccinia virus Tiantan strain (rVVT) using homologous recombination: rVVT-ΔvN1L (deletion of VVT N1L), rVVT-vN1Lr (insertion of enhanced green fluorescent protein, EGFP), and rVVT-gN1L (substitution with gN1L). The biological properties of these recombinant strains were systematically compared with those of wild-type VVT to evaluate the functional role of gN1L. Bioinformatics analysis revealed that the gN1L-encoded protein shares 26.80% homology and 45.10% similarity with the VVT N1L (vN1L)-encoded protein. Notably, the gN1 protein was predicted to be structurally stable, whereas the vN1 protein was classified as unstable. Growth curve assays demonstrated that gN1L significantly enhances VVT replication in BHK-21, HeLa, and PK-15 cells. RNA-seq analysis further suggested that this enhancement is potentially mediated through the PI3K/AKT signaling pathway. In vitro and in vivo virulence assays indicated that gN1L increases VVT virulence by up to 133-fold, representing a 7.5-fold greater effect compared to vN1L. Additionally, viral load measurements in host tissues revealed that gN1L facilitates VVT traversal across the blood–brain barrier by enhancing its ability to infect glial and endothelial cells. Collectively, these findings provide novel insights into the functional role of gN1L and offer valuable implications for the development of safer attenuated vaccines against GTPV.